Physicochemical properties of poly(lactic acid-co-glycolic acid) film modified via blending with poly(butyl acrylate-co-methyl methacrylate) - Zhu,Guoquan (2013)
A series of poly(lactic acid-co-glycolic acid) (PLGA)/poly(butyl acrylate-co-methyl methacrylate) (P(BA-co-MMA)) blend films with different P(BA-co-MMA) mole contents were prepared by casting the polymer blend solution in chloroform. Surface morphologies of the PLGAP(BA-co-MMA) blend films were studied by scanning electron microscopy (SEM). Thermal, mechanical, and chemical properties of PLGAP(BA-co-MMA) blend films were investigated by differential scanning calorimeter (DSC), thermogravimetric analysis (TGA), tensile tests, and surface contact angle tests. The introduction of P(BA-co-MMA) could modify the properties of PLGA films.